Modified graphene / polymer composites, methods of making and using the same
Patent Information
- Application Number
- CN202310316763.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-03-28
AI Technical Summary
[0005]1.石墨烯/聚丙烯复合材料的低成本、规模化制备一直难以实现
[0073]通过将石墨烯的剥离和石墨烯改性聚烯烃(例如聚丙烯)母粒的制备相结合的技术方案,避免了高昂的石墨烯或者石墨烯衍生物的使用,极大地简化了工艺流程,降低了聚合物纳米复合材料的生产成本。
Smart Images

Figure CN118725448B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a modified graphene / polymer composite and the prepared modified graphene / polymer composite, and more particularly to a method for preparing a modified graphene / polyolefin (e.g., polypropylene) composite and the obtained modified graphene / polyolefin (e.g., polypropylene) composite, belonging to the field of polyolefin compositions. Background Technology
[0002] Polypropylene, a widely used thermoplastic, possesses advantages such as high strength, high wear resistance, chemical resistance, good processing performance, lightweight, and high cost-effectiveness, leading to its extensive development and utilization in numerous industries including machinery, automotive, rail transportation, construction, electronics, and packaging. However, polypropylene's low melting point, poor light and heat stability, high low-temperature brittleness, and poor antistatic properties, along with its rigidity and strength, still fall short of current requirements, limiting its application in some complex environments and high-end fields. Therefore, achieving high performance and functionalization of polypropylene has significant industrial value. Graphene, a two-dimensional nanomaterial formed by the close packing of carbon atoms, possesses many excellent properties, such as an extremely large specific surface area (2630 m²). 2 / g), extremely high Young's modulus (1TPa) and fracture strength (130GPa), and extremely high carrier mobility (200,000cm³ / g). 2 Graphene possesses a high thermal conductivity (5300 W / (m·K)) and an extremely high thermal conductivity (5300 W / (m·K)). Therefore, adding graphene as a functional filler to polypropylene can significantly improve its strength, toughness, thermal conductivity, electrical conductivity, gas barrier properties, flame retardancy, electromagnetic shielding, and UV aging resistance, providing an ideal solution for the functionalization and high-performance of polypropylene.
[0003] In the preparation of polymer nanocomposites, the complete exfoliation and good dispersion of graphene are two key factors for polymer reinforcement and functionalization. This requires solving the challenges of large-scale preparation of high-quality graphene and the preparation of high-performance graphene-reinforced polymer nanocomposites, respectively. Currently, these two preparation processes are usually carried out independently. Graphene preparation can be achieved through methods such as micromechanical exfoliation, liquid-phase exfoliation, chemical vapor deposition, and epitaxial growth. However, the high production cost, low yield, complex production process, severe pollution, significant in-plane defects, and small lateral dimensions of graphene products greatly limit its industrial production and application. On the other hand, during the graphene-polymer composite process, graphene easily aggregates in the polymer matrix due to strong inter-sheet conjugation interactions. To solve the graphene dispersion problem and obtain high-performance polymer nanocomposites, most technical solutions tend to employ in-situ polymerization, solution mixing, and melt mixing methods. However, the former methods are complex, time-consuming, and use large amounts of toxic chemical reagents, making them unsuitable for industrial-scale and low-cost production. While multi-step and prolonged melt mixing techniques can improve the dispersion of graphene to some extent, the improvement is limited. Furthermore, prolonged melt shearing can cause dimensional reduction of graphene, significantly diminishing its intrinsic properties and leading to adverse effects. In addition, the chemical inertness of graphene's surface results in weak interfacial interactions with the polymer matrix, leading to suboptimal performance in the prepared composite material, and even severe deterioration of some performance indicators, significantly reducing its usability. Therefore, surface modification of the exfoliated graphene (CN112064338A and CN112174286A) is necessary to promote graphene dispersion and enhance the interfacial forces between graphene and the polymer matrix. However, graphene surface modification processes are lengthy, energy-intensive, and complex, resulting in additional costs.
[0004] The problem with the existing technology is:
[0005] 1. Low-cost, large-scale preparation of graphene / polypropylene composites has been a persistent challenge. In existing technologies, the preparation of high-quality graphene and the production of high-performance polypropylene nanocomposites are independent and fragmented. The complex and costly graphene production process severely restricts the large-scale production and practical application of polypropylene composites.
[0006] 2. The problem of uneven dispersion and easy agglomeration of graphene in a polypropylene matrix has remained unresolved. Since graphene production and application are separate processes, existing techniques generally employ chemical modification methods to enhance the interfacial interaction between graphene and polypropylene and promote good graphene dispersion in the polypropylene matrix. However, such surface modification significantly reduces the functionality of graphene, affecting the effectiveness of graphene-modified polypropylene. More importantly, existing surface chemical modification methods are generally cumbersome, difficult to operate, costly, and environmentally unfriendly, incompatible with existing polypropylene production and processing technologies, and unable to meet the needs of large-scale production of polypropylene nanocomposites.
[0007] 3. Poor compatibility and interfacial interaction between graphene and the polypropylene matrix prevent the effective integration of graphene functionality with the matrix, thus hindering a significant improvement in the overall performance of the composite material. Due to the low quality and poor dispersibility of the exfoliated graphene, a higher graphene mass fraction is typically used to achieve the desired polypropylene / graphene composite properties. This not only significantly increases costs but also severely deteriorates the inherent properties of polypropylene, such as fracture toughness, processability, and lightweight characteristics, thereby reducing the overall performance of the polypropylene composite material.
[0008] To address the aforementioned issues, CN113276376A proposed an in-situ method for exfoliating and uniformly dispersing expanded graphite during polymer melt processing. However, this method is superior because the graphene sheets in expanded graphite are still highly stacked (often dozens of graphene sheets are stacked together due to interlayer conjugation attraction). The moisture contained between the thick layers cannot exfoliate the stacked graphene into single or few-layer graphene sheets under high temperature. Furthermore, the interaction between graphene and polypropylene is weak and they are incompatible with each other. Therefore, it is difficult for composite materials to effectively achieve the exfoliation, dispersion, interfacial load transfer, and final improvement of macroscopic properties of graphene sheets.
[0009] Currently, there is a lack of a simpler and more efficient method to prepare highly exfoliated and well-dispersed graphene-polypropylene nanocomposites, especially a green and economical production method that combines graphene exfoliation, interface modification, and compounding to achieve high-performance graphene-polypropylene composites. Summary of the Invention
[0010] To address the aforementioned problems, this invention provides a simple method for preparing a modified graphene / polymer composite. Specifically, it involves using a polypropylene compatibilizer emulsion to assist in the exfoliation of low-oxidation expanded graphite to obtain compatibilizer-modified graphene, which is then blended with polypropylene to obtain a modified graphene / polypropylene composite.
[0011] This invention effectively combines high-quality exfoliation of expanded graphite, interface modification, and the preparation of high-performance graphene composites. It proposes a simple, low-cost, and high-throughput method for preparing modified graphene / polypropylene composites. Using low-oxidation expanded graphite (LOEG) as a precursor, it leverages the increased interlayer spacing (significantly weakening interlayer forces) and the hydrogen-bonded interactions between compatibilizers such as maleic anhydride-grafted polypropylene and the oxygen-containing functional groups on the LOEG surface. Through simple mechanical mixing, efficient exfoliation, uniform dispersion, and interface enhancement of graphene are achieved in one step, yielding high-performance graphene-modified polypropylene masterbatch. Then, melt blending with a polypropylene matrix achieves efficient preparation of modified graphene / polypropylene composites. This invention features a short process flow, simple operation, and is green and economical, effectively solving the problem of low-cost, large-scale preparation of high-quality graphene / polymer nanocomposites.
[0012] This invention aims to solve the problems of difficult graphene dispersion, cumbersome and costly graphene surface modification processes, and difficulty in industrial application in the existing graphene / polypropylene composite preparation process. It combines the efficient exfoliation of high-quality graphene with the preparation process of high-performance polypropylene nanocomposites to obtain functionalized modified graphene / polyolefin (e.g., polypropylene) composites.
[0013] To achieve the above objectives, this invention modifies the surface of expanded graphite with a small number of oxygen-containing functional groups through a controlled oxidation process. This process weakens the interlayer interactions of graphite, effectively reducing the mechanical processing time and energy required for the exfoliation of chemically expanded graphite. Furthermore, while maintaining the integrity of the graphene structure and properties, the small number of oxygen-containing functional groups simultaneously achieve high-quality exfoliation, stable dispersion, and surface modification of graphene through interactions such as hydrogen bonding with the compatibilizer. This compatibilizer-modified graphene masterbatch can effectively improve the mechanical strength, toughness, electrical conductivity, and thermal conductivity of the polypropylene matrix. This invention significantly shortens the production process of graphene / polypropylene composites, reduces production costs, and has significant industrial application value.
[0014] According to a first embodiment of the present invention, a method for preparing a modified graphene / polyolefin composite is provided, the method comprising the following steps:
[0015] (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree.
[0016] (2) The low-oxidation expanded graphite obtained in step (1) and the compatibilizer emulsion are mixed evenly and mechanically exfoliated to obtain a compatibilizer-modified graphene suspension (A); preferably, the concentration of graphene in the graphene suspension (A) is 0.01-200 mg / ml (preferably 0.1-150 mg / ml, more preferably 1-120 mg / ml, more preferably 5-100 mg / ml, more preferably 10-80 mg / ml, more preferably 15-60 mg / ml, more preferably 10-50 mg / ml, for example 20, 30, 40 mg / ml);
[0017] (3) The compatibilizer-modified graphene suspension (A) obtained in step (2) is dried to obtain (dried) compatibilizer-modified graphene particles (B), and
[0018] (4) The compatibilized graphene particles (B) obtained in step (3) are melt-blended with polyolefins (e.g., polypropylene, propylene copolymer, polyethylene, ethylene copolymer, etc., as a matrix) to obtain a modified graphene / polyolefin composite (C).
[0019] The preparation method described above is particularly suitable for preparing modified graphene / polypropylene composites. Therefore, this invention provides a method for preparing modified graphene / polypropylene composites, comprising the following steps:
[0020] (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree.
[0021] (2) The low-oxidation expanded graphite obtained in step (1) and the compatibilizer emulsion are mixed evenly and mechanically exfoliated to obtain a compatibilizer-modified graphene suspension (A); preferably, the concentration of graphene in the graphene suspension (A) is 0.01-200 mg / ml (preferably 0.1-150 mg / ml, more preferably 1-120 mg / ml, more preferably 5-100 mg / ml, more preferably 10-80 mg / ml, more preferably 15-60 mg / ml, more preferably 10-50 mg / ml, for example 20, 30, 40 mg / ml);
[0022] (3) The compatibilizer-modified graphene suspension (A) obtained in step (2) is dried to obtain (dried) a compatibilizer-modified graphene particle (B).
[0023] (4) The compatibilized graphene particles (B) obtained in step (3) are melt-blended with polypropylene (as matrix) to obtain the modified graphene / polypropylene composite (C).
[0024] More specifically, the present invention provides a method for preparing a modified graphene / polypropylene composite, the method comprising the following steps:
[0025] (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree.
[0026] (2) The low-oxidation expanded graphite and compatibilizer emulsion obtained in step (1) are mixed evenly at room temperature and mechanically exfoliated to obtain a compatibilizer-modified graphene suspension (A); preferably, the concentration of graphene in the graphene suspension (A) is 0.01-200 mg / ml (preferably 0.1-150 mg / ml, more preferably 1-120 mg / ml, more preferably 5-100 mg / ml, more preferably 10-80 mg / ml, more preferably 15-60 mg / ml, more preferably 10-50 mg / ml, for example 20, 30, 40 mg / ml);
[0027] (3) The compatibilizer-modified graphene suspension obtained in step (2) is dried to obtain compatibilizer-modified graphene particles (B);
[0028] (4) The compatibilizer-modified graphene particles are melt-blended with polypropylene (as matrix) to obtain the modified graphene / polypropylene composite (C).
[0029] In the methods described above, the compatibilizer emulsion used is a polymer compatibilizer emulsion.
[0030] In this application, the expanded graphite used in step (1) is one or more of chemically expanded graphene, thermally expanded graphite, and microwave expanded graphite (e.g., a combination of two or three).
[0031] In this application, the strong acid used in step (1) is one or a combination of concentrated sulfuric acid, concentrated hydrochloric acid, concentrated nitric acid, and concentrated phosphoric acid. Preferably, the volume of strong acid required per gram of expanded graphite is 80-350 ml, more preferably 100-320 ml, more preferably 120-300 ml, and more preferably 150-280 ml.
[0032] In this application, the strong oxidant in step (1) is one or more of potassium permanganate, potassium perchlorate, potassium ferrate, potassium dichromate, potassium nitrate, sodium nitrate, potassium persulfate, sodium persulfate, and ammonium persulfate (e.g., a combination of two, three, or four). The mass ratio (wt) of the strong oxidant to expanded graphite is (0.1-5):1, preferably (0.2-4.7):1, preferably (0.3-4.5):1, preferably (0.4-4.2):1, preferably (0.5-4.0):1, preferably (0.6-3.7):1, preferably (0.7-3.5):1, preferably (0.8-3.2):1, preferably (1-3):1. Preferably, the oxidation time is 20 minutes to 5 hours, more preferably 30 minutes to 4.5 hours, more preferably 1 hour to 4 hours, for example, 2 or 3 hours.
[0033] The degree of oxidation of expanded graphite is determined by the amount of strong oxidizing agent and the oxidation time. The less strong oxidizing agent and the shorter the oxidation time, the lower the degree of oxidation. The degree of oxidation can also be determined by the carbon-oxygen ratio in the material.
[0034] Preferably, in step (1), the degree of "low oxidation" in the low-oxidation expanded graphite refers to a carbon-to-oxygen atom ratio in the oxidized expanded graphite between 1.5 and 8:1, preferably between 2.5 and 6:1, preferably between 3 and 5.5:1, preferably between 3.2 and 5:1, and more preferably between 3.5 and 4.5:1. If the degree of oxidation is too high, it will damage the lattice integrity and conductivity of the exfoliated graphene.
[0035] In this invention, the carbon-to-oxygen atomic ratio in the oxidized expanded graphite can be obtained by X-ray photoelectron spectroscopy or elemental analysis (atomic emission spectroscopy). X-ray photoelectron spectroscopy can be performed using instruments such as the German SPECTRO XRF-X-ray spectrometer or the Thermo Scientific ESCALAB Xi+. Elemental analysis can be performed using instruments such as the German SPECTRO emission spectrometer or the Agilent 5800ICP-OES.
[0036] Preferably, the compatibilizer emulsion is a (low molecular weight) polyolefin-type compatibilizer emulsion (i.e., ungrafted or grafted polyolefin-type compatibilizer emulsion) or a polyether-type compatibilizer emulsion. More preferably, the compatibilizer emulsion is selected from one or more of the following polymer compatibilizer emulsions: polyethylene wax emulsion, polypropylene wax emulsion, ethylene-vinyl acetate copolymer emulsion, isooctylphenyl polyoxyethylene ether (e.g., Triton), polyoxyethylene polyether, polyoxypropylene polyether or polyoxyethylene polyoxypropylene (e.g., poloxamer), maleic anhydride-grafted polyethylene emulsion, maleic anhydride-grafted polypropylene emulsion, maleic anhydride-grafted ethylene-vinyl acetate copolymer emulsion, maleic anhydride-grafted ethylene-butene copolymer emulsion, and maleic anhydride-grafted ethylene-octene copolymer emulsion.
[0037] Accordingly, the compatibilizer is a (low molecular weight) polyolefin compatibilizer (i.e., an ungrafted or grafted polyolefin compatibilizer) or a polyether compatibilizer.
[0038] The solid content of the emulsion is 1-50 wt%, preferably 3-48 wt%, preferably 5-46 wt%, preferably 7-45 wt%, preferably 9-43 wt%, preferably 10-40 wt%, preferably 15-37 wt%, preferably 18-35 wt%, preferably 20-30 wt%.
[0039] The mass ratio of the solid component to the low-oxidation expanded graphite in the compatibilizer emulsion is (0.4-9):1, preferably (0.8-8.5):1, preferably (1.2-8):1, preferably (1.5-7):1, preferably (1.7-6):1, preferably (1.8-5):1, preferably (2.0-4.0):1.
[0040] Preferably, in step (2), the low-oxidation-expansion graphite and compatibilizer emulsion obtained in step (1) are mixed uniformly at 5-100°C, more preferably 6-80°C, more preferably 7-60°C, more preferably 10-50°C, more preferably 15-40°C, and more preferably at room temperature (20-30°C).
[0041] Preferably, in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the obtained compatibilizer-modified graphene suspension (A) (i.e., the concentration of graphene in the graphene suspension (A)) is 0.01-250 mg / ml, preferably 0.05-230 mg / ml, preferably 0.1-200 mg / ml, preferably 0.5-190 mg / ml, preferably 0.8-180 mg / ml. g / ml, preferably 1-170 mg / ml, preferably 1.5-165 mg / ml, preferably 2.0-160 mg / ml, for example 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 22, 25, 27, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 90, 100, 110, 120, 130, 140, 150 mg / ml.
[0042] The mechanical stripping described in step (2) includes one or a combination of ball milling, sand milling, water bath ultrasonication, probe ultrasonication, high-speed shearing, high-pressure homogenization, and Taylor-Couette fluid stripping.
[0043] The drying process described in step (3) includes one or a combination of vacuum drying, freeze drying, forced air drying, fluidized bed drying, spray drying, infrared drying, and microwave drying.
[0044] In this invention, the melt blending in step (3) includes one or more of the following processes: internal mixing, single-screw extrusion, and twin-screw extrusion. The processing temperature is 180-220℃, and the processing time is 3-20 minutes.
[0045] Preferably, the polyolefin used in step (4) (as a matrix) is: polyolefin plastic and / or polyolefin elastomer. Polyolefin elastomer refers to a thermoplastic elastomer that is polymerized in situ using metallocene catalysts to polymerize ethylene and α-olefins. It exhibits thermoplastic elastomer behavior through physical crosslinking and has the properties of both plastics and rubber.
[0046] Ethylene propylene rubber (EPR) is a type of rubber formed by chemical cross-linking, and can be divided into binary EPR and ternary EPR.
[0047] Preferably, the polyolefin plastic (as matrix) is selected from one or more of polypropylene, propylene copolymer, polyethylene, ethylene copolymer, ethylene-vinyl acetate copolymer, poly-1-butene, and 1-butene copolymer. The polyolefin elastomer (as matrix) is selected from one or more of ethylene-1-butene elastomer, ethylene-1-octene elastomer, and ethylene / propylene elastomer.
[0048] Preferably, in the compatibilizer-modified graphene particles (B), the mass percentage of graphene is in the range of 5-70 wt%, preferably 7-65 wt%, preferably 8-60 wt%, preferably 9-55 wt%, preferably 10-50 wt%, preferably 15-45 wt%, preferably 20-40 wt%, preferably 25-35 wt%, for example 13, 17, 22, 27, 30, 32 wt%, based on the total weight of the compatibilizer-modified graphene particles (B).
[0049] In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin (e.g., polypropylene) should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin (e.g., polypropylene) composite (C) (i.e., the mass fraction or content of graphene in composite C) is 0.05-25 wt%, preferably 0.1-20 wt%, preferably 0.15-15 wt%, preferably 0.20-13 wt%. Preferably 0.25-12wt%, preferably 0.30-10wt%, preferably 0.35-9wt%, preferably 0.40-8wt%, for example 0.50, 0.60, 0.70, 0.80, 0.90, 1.0, 1.2, 1.5, 1.8, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5wt%, based on the total weight of the complex (C).
[0050] More specifically, the present invention provides a method for preparing a modified graphene / polyolefin (e.g., polypropylene) composite, characterized by the following specific steps:
[0051] (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree.
[0052] (2) The low-oxidation expanded graphite and compatibilizer emulsion obtained in step (1) are mixed evenly at room temperature and mechanically exfoliated to obtain a compatibilizer-modified graphene suspension, and the concentration of graphene is controlled to be 0.01-200 mg / ml.
[0053] (3) The compatibilizer-modified graphene suspension obtained in step (2) is dried to obtain compatibilizer-modified graphene particles, which are then melt-blended with (as a matrix) polyolefin (e.g., polypropylene) to obtain a modified graphene / polyolefin (e.g., polypropylene) composite.
[0054] Preferably, the expanded graphite in step (1) is one or a combination of chemically expanded graphene, thermally expanded graphite, and microwave expanded graphite.
[0055] Preferably, the strong acid in step (1) is one or a combination of concentrated sulfuric acid, concentrated hydrochloric acid, concentrated nitric acid, and concentrated phosphoric acid, and the volume of the strong acid required per gram of expanded graphite is 100-300 ml.
[0056] Preferably, the strong oxidant in step (1) is one or a combination of potassium permanganate, potassium perchlorate, potassium ferrate, potassium dichromate, potassium nitrate, sodium nitrate, potassium persulfate, sodium persulfate, and ammonium persulfate, and the mass ratio of the strong oxidant to expanded graphite is (0.1-5):1, and the oxidation time is 20 minutes to 5 hours.
[0057] Preferably, the compatibilizer in step (2) is one or a combination of polyethylene wax emulsion, polypropylene wax emulsion, ethylene-vinyl acetate copolymer emulsion, isooctylphenyl polyoxyethylene ether (e.g., Triton), various polyethers (e.g., polyethylene oxide or polypropylene oxide) or polyoxyethylene polyoxypropylene (e.g., poloxamer), maleic anhydride-grafted polyethylene emulsion, maleic anhydride-grafted polypropylene emulsion, maleic anhydride-grafted ethylene-vinyl acetate copolymer emulsion, maleic anhydride-grafted ethylene-butene copolymer emulsion, and maleic anhydride-grafted ethylene-octene copolymer emulsion, the solid content of the emulsion is 1-50%, and the mass ratio of the compatibilizer to low-oxide graphene is (1-9):1.
[0058] Preferably, the mechanical stripping in step (2) includes one or a combination of ball milling, sand milling, water bath ultrasonication, probe ultrasonication, high-speed shearing, high-pressure homogenization, and Taylor-Couette fluid stripping.
[0059] Preferably, the drying process in step (3) includes one or a combination of vacuum drying, freeze drying, forced air drying, fluidized bed drying, spray drying, infrared drying, and microwave drying.
[0060] Preferably, the melt blending in step (3) includes one or more of the following: internal mixing, single-screw extrusion, and twin-screw extrusion, with a processing temperature of 180-220°C and a processing time of 3-20 minutes.
[0061] Preferably, the graphene content in the modified graphene / polyolefin (e.g., polypropylene) composite obtained in step (3) is 0.01-20%.
[0062] According to a second embodiment of the invention, the invention also provides a (compatibilizer) modified graphene / polyolefin composite obtained by the above method. The mass percentage or weight percentage of graphene (i.e., the mass fraction or content of graphene in composite C) is 0.05-25 wt%, preferably 0.1-20 wt%, preferably 0.15-15 wt%, preferably 0.20-13 wt%, preferably 0.25-12 wt%, preferably 0.30-10 wt%, preferably 0.35-9 wt%, preferably 0.40-8 wt%, for example 0.50, 0.60, 0.70, 0.80, 0.90, 1.0, 1.2, 1.5, 1.8, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5 wt%, based on the total weight of composite (C).
[0063] According to a third embodiment of the present invention, the present invention also provides compatibilizer-modified graphene particles (B). These are prepared by a method comprising the following steps:
[0064] (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree.
[0065] (2) Mix the low-oxidation expanded graphite obtained in step (1) with the compatibilizer emulsion evenly, and then mechanically exfoliate to obtain a compatibilizer-modified graphene suspension (A).
[0066] (3) The compatibilizer-modified graphene suspension (A) obtained in step (2) is dried to obtain (dried) compatibilizer-modified graphene particles (B).
[0067] In other words, the compatibilizer-modified graphene particles (B) are prepared by steps (1)-(3) of the method described above according to the first embodiment.
[0068] The compatibilizer used in this application is a (low molecular weight) polyolefin compatibilizer (i.e., ungrafted or grafted polyolefin compatibilizer) or a polyether compatibilizer. The aforementioned compatibilizer emulsion is formed by emulsifying the polyolefin compatibilizer (i.e., ungrafted or grafted polyolefin compatibilizer) or the polyether compatibilizer in water with an emulsifier or surfactant. The solid content of the emulsion is as described above, for example, 1-50 wt%.
[0069] Preferably, the number average molecular weight of the compatibilizer, i.e., the number average molecular weight of the polyolefin-type compatibilizer or the polyether-type compatibilizer, is generally between 1,000 and 70,000, more preferably between 1,200 and 60,000, and even more preferably between 1,500 and 50,000, for example, 2,000, 3,000, 4,000, 5,000, 6,000, 7,000, 8,000, 9,000, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, and 40,000. Polyolefin-type compatibilizers are, for example, polypropylene wax and / or polyethylene wax (polypropylene wax, polyethylene wax, ethylene-propylene copolymer wax, polyethylene copolymer wax, etc.).
[0070] The emulsifier or surfactant used to formulate the above-mentioned compatibilizer emulsion is one or a combination of several ionic surfactants (including sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium cholate, hexadecyltrimethylammonium bromide, etc.) and nonionic surfactants (isodecyl alcohol polyoxyethylene ether, octadecyl alcohol polyoxyethylene ether, isooctylphenyl polyoxyethylene ether, isooctylphenyl polyoxyethylene ether, etc.).
[0071] The technical solution of this invention can be directly used to reinforce polyolefins (such as polymer matrices or substrates such as polypropylene or polyethylene) for the preparation of polymer nanocomposites. It can also be directly used in the field of functional inks and coatings. Alternatively, the product of this solution can be used as a raw material to produce high-performance modified polyolefin fibers (such as polypropylene fibers) through spinning technology, or to produce nonwoven fabrics that are resistant to pathogens (bacteria, viruses) through meltblown technology, or to be used in other related fields through other technical means.
[0072] The preparation method of the present invention has the following advantages compared with the prior art:
[0073] The technical solution that combines the exfoliation of graphene with the preparation of graphene-modified polyolefin (e.g., polypropylene) masterbatch avoids the use of expensive graphene or graphene derivatives, greatly simplifies the process, and reduces the production cost of polymer nanocomposites.
[0074] Unlike the cumbersome modification process of traditional graphene surfaces, this approach achieves efficient exfoliation and dispersion of expanded graphite through a simple structural design of the precursor expanded graphite, enhancing the interaction between graphene and polyolefin (e.g., polypropylene) matrix, and effectively solving the problem of polymer nanocomposite material preparation.
[0075] The preparation method proposed in this scheme is simple, efficient, environmentally friendly, and low-cost, and has strong potential for industrial application. The polymer nanocomposite material obtained by this scheme has excellent comprehensive properties and a wide range of applications.
[0076] Regarding the method of using a polypropylene compatibilizer emulsion to mechanically exfoliate and disperse expanded graphite as mentioned in the embodiments of the present invention, a similar effect can be achieved by directly using a polypropylene solution (or suspension) for mechanical processing, but it is not preferred. Furthermore, regarding the method of exfoliation via liquid-phase mechanical processing mentioned in the embodiments of the present invention, it can also be achieved through polymer melt processing.
[0077] Here, "polypropylene solution" (or suspension) refers to a solution formed by dissolving polypropylene in toluene and / or xylene under heating conditions. "Polypropylene suspension" refers to a suspension formed by adding polypropylene to toluene or xylene.
[0078] Advantages of the present invention
[0079] 1. This invention does not require expensive graphene or graphene derivatives as raw materials, and can exfoliate expanded graphite into high-quality graphene during liquid phase processing.
[0080] 2. This invention avoids the cumbersome modification process of graphene, and instead organically combines the exfoliation and modification of graphene, and combines the production and application of materials, thus realizing the integrated preparation of graphene / polypropylene composite materials.
[0081] 3. The preparation method proposed in this invention is simple, efficient, green, environmentally friendly, and low in cost, and has significant industrial application value;
[0082] 4. The composite obtained by this invention has uniformly dispersed graphene, strong interfacial interactions, excellent comprehensive material performance, and a wide range of applications.
[0083] All raw materials involved in this invention are commercially available. For example: expanded graphite (Qingdao Jinke Graphite Co., Ltd.); strong acids such as sulfuric acid and oxidants such as potassium permanganate (Sinopharm Chemical Reagent Co., Ltd.); maleic anhydride-grafted polypropylene emulsion (Shanghai Joule Wax Industry Co., Ltd.); isotactic polypropylene (China Petroleum & Chemical Corporation Zhenhai Refining & Chemical Co., Ltd.). Attached Figure Description
[0084] Figure 1 These are (a) TEM images of the MOG sheet and (b) HRTEM images of the edges in Example 1.
[0085] Figure 2 These are the selected area electron diffraction pattern (c) and the intensity diagrams of the diffraction peaks (1010) and (2110) corresponding to Example 1.
[0086] Figure 3 The (a) TGA curves are of PP-g nanocomposites with different MOG contents.
[0087] Figure 4 (b) DTG curves of PP-g nanocomposites with different MOG contents.
[0088] Figure 5 This is a comparison chart of (c)Tonset, T-50, and Tmax of PP-g nanocomposites with different MOG contents.
[0089] Figure 6 (a) Stress-strain curves of PP-g nanocomposites with different MOG contents.
[0090] Figure 7 (b) Tensile strength and Young's modulus of PP-g nanocomposites with different MOG contents. Detailed Implementation
[0091] The present invention will be further described in detail through the following embodiments, but the present invention is not limited to these embodiments.
[0092] The devices used in the embodiments are all commonly used in the art and commercially available, unless otherwise specified.
[0093] Raw materials used in the examples:
[0094] Expanded graphite can be prepared by conventional methods, and chemically expanded graphite can be prepared by the method disclosed in our research group's Chinese patent publication (CN105253878A). An exemplary preparation method is as follows: 20 mL of hydrogen peroxide solution (Sinopharm Chemical Reagent Co., Ltd., 30% concentration) is added to 180 mL of concentrated sulfuric acid (Sinopharm Chemical Reagent Co., Ltd., 98% concentration) and mixed evenly. Then, 2 g of flake graphite (Sigma-Aldrich reagent, grade 808113) is added, and the mixture is allowed to stand for expansion for 24 hours. After separation, chemically expanded graphite is obtained.
[0095] Thermally expandable graphite is obtained by heating expandable graphite (purchased from Qingdao Jintao Graphite Co., Ltd.) at 800℃ for 60 seconds.
[0096] Microwave-expandable graphite is obtained by expanding expandable graphite (purchased from Qingdao Jintao Graphite Co., Ltd.) in a 60Hz microwave oven for 5 seconds.
[0097] Sulfuric acid and potassium permanganate: Sinopharm Chemical Reagent Co., Ltd.
[0098] Maleic anhydride-grafted polypropylene (MAPP) emulsion with a solid content of 5%: Shanghai Joule Wax Industry Co., Ltd., grade EP15.
[0099] Isotropic polypropylene: China Petroleum & Chemical Corporation Zhenhai Refining & Chemical Co., Ltd., grade T30S.
[0100] Maleic anhydride grafted polyethylene (MAPE) emulsion with a solid content of 10%: Shanghai Joule Wax Industry Co., Ltd., EM21335, solid content 35%, diluted to 10% before use.
[0101] Ethylene-vinyl acetate (EVA) emulsion with a solid content of 20%: Shandong Yueyang New Material Co., Ltd., BJ-806H, with a solid content of 60%, diluted to 20% before use.
[0102] Example 1
[0103] 1) Dissolve 2g of potassium permanganate in 400ml of concentrated sulfuric acid (98wt%), then add 2g of chemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 1 hour. Then, slowly add the mixture to ice water to quench the reaction. Add 10ml of hydrogen peroxide (30% concentration) and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium permanganate and the reaction time. As a measure of oxidation, the carbon-to-oxygen atomic ratio of the product (obtained by SPECTRO emission spectrometry, Germany) is 3.9:1.
[0104] 2) Add the above MOCEG to 40g of maleic anhydride-grafted polypropylene (MAPP) emulsion (Shanghai Joule Wax Industry Co., Ltd., brand P15) with a solid content of 5%, stir evenly, and then treat the mixture with a probe ultrasonic (350W) for 2h to obtain MAPP / graphene dispersion. Place the dispersion in an 80℃ forced-air oven and dry for 48 hours to obtain MAPP-modified graphene particles, in which the mass percentage of graphene is about 50wt%.
[0105] 3) 4g of modified graphene particles and 36g of polypropylene (isotactic polypropylene: China Petroleum & Chemical Corporation Zhenhai Refining & Chemical Co., Ltd., grade T30S) were premixed at high speed for 5min at room temperature, and then kneaded at 200℃ for 8min to obtain a modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 5wt%. The code is PP-g-MOG-5.0.
[0106] Example 2
[0107] 1) Dissolve 15g of potassium dichromate in 450ml of concentrated sulfuric acid, then add 3g of thermally expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 20 minutes. Then, slowly add the mixture to ice water to quench the reaction. Next, add 75ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium dichromate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 4.7:1.
[0108] 2) Add the above MOCEG to 70g of maleic anhydride-grafted polyethylene (MAPE) emulsion (Shanghai Joule Wax Industry Co., Ltd., EM21335) with a solid content of 10%, stir evenly, and then treat the mixture with water bath ultrasonic (600W) for 5h to obtain MAPE / graphene dispersion. Freeze-dry the dispersion for 72 hours to obtain MAPE-modified graphene particles, in which the mass percentage of graphene is about 30wt%.
[0109] 3) 10g of modified graphene particles and 290g of polypropylene were premixed at high speed for 5min at room temperature, and then co-mixed at 190℃ for 5min in a twin-screw extruder to obtain a modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 1wt%. The code name is PP-g-MOG-1.0.
[0110] Example 3
[0111] 1) Dissolve 5g of potassium perchlorate in 1000ml of concentrated sulfuric acid, then add 10g of microwave-expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 2 hours. Then, slowly add the mixture to ice water to quench the reaction, followed by adding 2ml of 30% hydrogen peroxide and stirring for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium perchlorate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.7:1.
[0112] 2) Add the above MOCEG to 450g of ethylene-vinyl acetate (EVA) emulsion (Shandong Yueyang New Material Co., Ltd., brand name BJ-707) with a solid content of 20%, stir evenly, and then treat the mixture in a sand mill at 2500 rpm for 10h to obtain an EVA / graphene dispersion. After microwave drying of the dispersion, EVA-modified graphene particles are obtained, in which the mass percentage of graphene is about 10wt%.
[0113] 3) 20g of modified graphene particles and 18g of polypropylene were premixed at high speed for 5min at room temperature, and then kneaded at 210℃ for 10min to obtain the modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 10wt%.
[0114] Example 4
[0115] 1) Dissolve 0.5g of potassium ferrate in 250ml of concentrated sulfuric acid, then add 2g of chemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 3 hours. Then, slowly add the mixture to ice water to quench the reaction. Add 2.5ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium ferrate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.8:1.
[0116] 2) Add the above MOCEG to 20g of a 15% maleic anhydride-grafted ethylene-vinyl acetate copolymer (MA-g-EVA) emulsion (Shandong Yueyang New Material Co., Ltd., BJ-806H), stir evenly, and then shear the mixture using a high-speed shearing device at 11000 rpm for 3 hours to obtain a MA-g-EVA / graphene dispersion. Freeze-dry the dispersion for 48 hours to obtain MA-g-EVA modified graphene particles, wherein the mass percentage of graphene is approximately 40%.
[0117] 3) 5g of modified graphene particles and 395g of polypropylene were premixed at high speed for 5min at room temperature, and then co-mixed at 195℃ for 5min in a twin-screw extruder to obtain a modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 0.5%. The code is PP-g-MOG-0.5.
[0118] Example 5
[0119] 1) Dissolve 4g of potassium permanganate in 500ml of concentrated sulfuric acid, then add 2g of thermochemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 40 minutes. Then, slowly add the mixture to ice water to quench the reaction. Next, add 20ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium permanganate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.3:1.
[0120] 2) Add the above MOCEG to 100g of isooctylphenyl polyoxyethylene ether (X-100) emulsion (Sinopharm Chemical Reagent Co., Ltd., brand name 30188928) with a solid content of 8%, stir evenly, and then treat the mixture in a ball mill at 400 rpm for 24h to obtain X-100 / graphene slurry. Place the slurry in an 80℃ forced-air oven and dry for 48 hours to obtain X-100 modified graphene particles, in which the mass ratio of graphene is about 20%.
[0121] 3) 4g of modified graphene particles and 36g of polypropylene were premixed at high speed for 5min at room temperature, and then kneaded at 185℃ for 10min to obtain the modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 2%.
[0122] Example 6
[0123] 1) Dissolve 6g of potassium perchlorate in 550ml of concentrated sulfuric acid, then add 2g of chemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 30 minutes. Then, slowly add the mixture to ice water to quench the reaction. Next, add 30ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is determined by the amount of potassium perchlorate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.9:1.
[0124] 2) Add the above MOCEG to 25g of polypropylene wax (PPW) emulsion (Shanghai Tongyi Chemical, brand name Lakewax 78) with a solid content of 24%, stir evenly, and then treat the mixture in a ball mill at 400 rpm for 24h to obtain PPW / graphene slurry. Vacuum dry the slurry for 36 hours to obtain PPW modified graphene particles, in which the mass percentage of graphene is about 25%.
[0125] 3) 4.8g of modified graphene particles and 35.2g of polypropylene were premixed at high speed for 5min at room temperature, and then kneaded at 200℃ for 8min to obtain a modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 3wt%. The code name is PP-g-MOG-3.0.
[0126] Example 7
[0127] 1) Dissolve 2g of potassium ferrate in 300ml of concentrated sulfuric acid, then add 2g of thermally expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 1 hour. Then, slowly add the mixture to ice water to quench the reaction. Next, add 10ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is determined by the amount of potassium ferrate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.8:1.
[0128] 2) Add the above MOCEG to 50g of polyethylene wax (PEW) emulsion (BASF, Poligen WE6) with a solid content of 8%, stir evenly, and then treat the mixture with a probe ultrasonic (350W) for 2h to obtain PEW / graphene dispersion. Fluidize and dry the dispersion for 10h to obtain PEW modified graphene particles, in which the mass percentage of graphene is about 33%.
[0129] 3) 6g of modified graphene particles and 44g of polypropylene were premixed at high speed for 5min at room temperature, and then kneaded at 210℃ for 7min to obtain the modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 4%.
[0130] Example 8
[0131] 1) Dissolve 3g of potassium dichromate in 400ml of concentrated sulfuric acid, then add 2g of microwave-expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 50 minutes. Then, slowly add the mixture to ice water to quench the reaction. Next, add 15ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is determined by the amount of potassium dichromate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.2:1.
[0132] 2) Add the above MOCEG to 400g of a 2% solid content poloxamer (F-127) emulsion (Sigma-Aldrich, grade P2443), stir evenly, and then subject the mixture to high-pressure spray treatment at a flow rate of 1L / h and a fluid pressure of 20MPa to obtain an F-127 / graphene dispersion. After spray drying the dispersion, obtain F-127 modified graphene particles, in which the mass percentage of graphene is approximately 20%.
[0133] 3) 10g of modified graphene particles and 190g of polypropylene were premixed at high speed for 5min at room temperature, and then co-mixed at 200℃ for 6min in a twin-screw extruder to obtain a modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 1%.
[0134] Example 9
[0135] 1) Dissolve 2g of potassium permanganate in 400ml of concentrated sulfuric acid, then add 2g of chemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 1 hour. Then, slowly add the mixture to ice water to quench the reaction. Next, add 10ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium permanganate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 4.0:1.
[0136] 2) Add the above MOCEG to 1000g of maleic anhydride-grafted polyethylene (MAPE) emulsion (Shanghai Joule Wax Industry Co., Ltd., EM21335) with a solid content of 1.8%, stir evenly, and then subject the mixture to high-pressure spraying at a flow rate of 10L / h and a fluid pressure of 200MPa to obtain a MAPE / graphene dispersion. After fluidizing and drying the dispersion, MAPE-modified graphene particles are obtained, in which the mass percentage of graphene is approximately 10%.
[0137] 3) 20g of modified graphene particles and 980g of polypropylene were premixed at high speed for 10min at room temperature, and then kneaded at 200℃ for 10min to obtain the modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 0.2%.
[0138] Example 10
[0139] 1) Dissolve 2g of potassium permanganate in 400ml of concentrated sulfuric acid, then add 2g of chemically expanded graphite (prepared by the above method) and mix thoroughly. Maintain the reaction temperature at 35℃ and stir continuously for 1 hour. Then, slowly add the mixture to ice water to quench the reaction. Next, add 10ml of 30% hydrogen peroxide and stir for 5 minutes. After filtration and washing, obtain a low-oxidation expanded graphite (MOCEG) product. The degree of oxidation is controlled by the amount of potassium permanganate and the reaction time. The carbon-to-oxygen atomic ratio of the product is 3.9:1.
[0140] 2) Add the above MOCEG to 100g of maleic anhydride-grafted ethylene-octene copolymer (MA-g-POE) emulsion (Shanghai Tongyi Chemical, Novaseal 2225) with a solid content of 2%, stir evenly, and then treat the mixture with a probe ultrasonic (350W) for 2h to obtain MA-g-POE / graphene dispersion. Freeze-dry the dispersion for 72 hours to obtain MA-g-POE modified graphene particles, in which the mass ratio of graphene is about 50%.
[0141] 3) 4g of modified graphene particles and 46g of polypropylene were premixed at high speed for 5min at room temperature, and then kneaded at 200℃ for 8min to obtain the modified graphene / polypropylene composite. The final mass fraction of graphene in the composite was 8%.
[0142] The performance test results of the various code-named products obtained from the above embodiments are shown in the accompanying drawings.
Claims
1. A method for preparing modified graphene / polyolefin composites, comprising the following steps: (1) Expanded graphite is intercalated and oxidized in a mixture of strong acid and strong oxidant to obtain expanded graphite with low oxidation degree; the "low oxidation degree" refers to the carbon-oxygen atom ratio in the oxidized expanded graphite being between 3 and 5.5:
1. (2) The low-oxidation expanded graphite obtained in step (1) and the compatibilizer emulsion are mixed evenly and mechanically exfoliated to obtain a compatibilizer-modified graphene suspension (A). The compatibilizer emulsion is formed by emulsifying a polyolefin-type compatibilizer or a polyether-type compatibilizer in water with an emulsifier or surfactant. The solid content of the compatibilizer emulsion is 1-50 wt%. The mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (0.4-9):
1. The amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the obtained compatibilizer... The concentration of graphene in the modified graphene suspension (A) is 0.01-250 mg / ml; (3) The compatibilizer-modified graphene suspension (A) obtained in step (2) is dried to obtain a compatibilizer-modified graphene particle (B), and (4) The compatibilizer-modified graphene particles (B) obtained in step (3) are melt-blended with the polyolefin as the matrix to obtain the modified graphene / polyolefin composite (C). In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 5-70 wt%, based on the total weight of the compatibilizer-modified graphene particles (B).
2. The preparation method according to claim 1, wherein, In step (1), "low oxidation degree" in low-oxidation expanded graphite means that the carbon-to-oxygen atom ratio in the oxidized expanded graphite is between 3.2 and 5:1; and / or In step (4), the polyolefin is a polyolefin plastic, a polyolefin elastomer, or a mixture of both.
3. The preparation method according to claim 2, wherein, In step (1), "low oxidation degree" in low oxidation degree expanded graphite means that the carbon-oxygen atom ratio in the oxidized expanded graphite is between 3.5 and 4.5:
1.
4. The preparation method according to claim 1 or 2, wherein, The expanded graphite used in step (1) is selected from one or more of chemically expanded graphene, thermally expanded graphite, and microwave-expanded graphite; and / or The strong oxidant mentioned in step (1) is one or more selected from potassium permanganate, potassium perchlorate, potassium ferrate, potassium dichromate, potassium nitrate, sodium nitrate, potassium persulfate, sodium persulfate, and ammonium persulfate; and / or The strong acid used in step (1) is selected from one or more of concentrated sulfuric acid, concentrated hydrochloric acid, concentrated nitric acid, and concentrated phosphoric acid; and / or the number average molecular weight of the polyolefin compatibilizer or polyether compatibilizer is between 1,000 and 70,000.
5. The preparation method according to claim 4, wherein the number average molecular weight of the polyolefin compatibilizer or the polyether compatibilizer is between 1200 and 60000.
6. The preparation method according to claim 5, wherein... The number average molecular weight of polyolefin-type compatibilizers or polyether-type compatibilizers is between 1500 and 50000.
7. The preparation method according to claim 2, wherein, Polyolefin plastics are selected from one or more of polypropylene, propylene copolymers, polyethylene, ethylene copolymers, ethylene-vinyl acetate copolymers, poly-1-butene, and 1-butene copolymers; and / or polyolefin elastomers are selected from one or more of ethylene-1-butene elastomers, ethylene-1-octene elastomers, and ethylene / propylene elastomers.
8. The preparation method according to any one of claims 1-3, wherein, The compatibilizer emulsion is selected from one or more of the following polymer compatibilizer emulsions: polyethylene wax emulsion, polypropylene wax emulsion, ethylene-vinyl acetate copolymer emulsion, isooctylphenyl polyoxyethylene ether, polyoxyethylene polyether, polyoxypropylene polyether, polyoxyethylene polyoxypropylene, maleic anhydride-grafted polyethylene emulsion, maleic anhydride-grafted polypropylene emulsion, maleic anhydride-grafted ethylene-vinyl acetate copolymer emulsion, maleic anhydride-grafted ethylene-butene copolymer emulsion, and maleic anhydride-grafted ethylene-octene copolymer emulsion.
9. The preparation method according to any one of claims 1-3, wherein, In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.05-25 wt%, based on the total weight of the composite (C).
10. The preparation method according to claim 9, wherein, The compatibilizer emulsion used in step (2) has a solid content of 3-48 wt%; and / or In step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (0.8-8.5):1; and / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the obtained compatibilizer-modified graphene suspension (A) is 0.05-230 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is 7-65 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.1-20 wt%, based on the total weight of the composite (C).
11. The preparation method according to claim 10, wherein, The solid content of the compatibilizer emulsion used in step (2) is 5-46 wt%; And / or in step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (1.2-8):1; And / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the resulting compatibilizer-modified graphene suspension (A) is 0.1-200 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 8-60 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.15-15 wt%, based on the total weight of the composite (C).
12. The preparation method according to claim 11, wherein, The compatibilizer emulsion used in step (2) has a solid content of 7-45 wt%; and / or In step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (1.5-7):1; and / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the obtained compatibilizer-modified graphene suspension (A) is 0.5-190 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 9-55 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.20-13 wt%, based on the total weight of the composite (C).
13. The preparation method according to claim 12, wherein, The compatibilizer emulsion used in step (2) has a solid content of 9-43 wt%; and / or In step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (1.7-6):1; and / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the resulting compatibilizer-modified graphene suspension (A) is 0.8-180 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 10-50 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.25-12 wt%, based on the total weight of the composite (C).
14. The preparation method according to claim 13, wherein, The solid content of the compatibilizer emulsion used in step (2) is 10-40 wt%; and / or In step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (1.8-5):1; and / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the resulting compatibilizer-modified graphene suspension (A) is 1-170 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 15-45 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.30-10 wt%, based on the total weight of the composite (C).
15. The preparation method according to claim 14, wherein, The solid content of the compatibilizer emulsion used in step (2) is 15-37 wt%; And / or in step (2), the mass ratio of the solid component in the compatibilizer emulsion to the low-oxidation expanded graphite is (2.0-4.0):1; and / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the obtained compatibilizer-modified graphene suspension (A) is 1.5-165 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is in the range of 20-40 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.35-9 wt%, based on the total weight of the composite (C).
16. The preparation method according to claim 15, wherein, The solid content of the compatibilizer emulsion used in step (2) is 18-35 wt%; And / or in step (2), the amount of low-oxidation expanded graphite relative to the compatibilizer emulsion should be such that the concentration of graphene in the resulting compatibilizer-modified graphene suspension (A) is 2.0-160 mg / ml; and / or In step (3), the mass percentage of graphene in the compatibilizer-modified graphene particles (B) is 25-35 wt%, based on the total weight of the compatibilizer-modified graphene particles (B); and / or In step (4), the amount of compatibilizer-modified graphene particles (B) relative to the polyolefin should be such that the mass percentage or weight percentage of graphene in the resulting modified graphene / polyolefin composite (C) is 0.40-8 wt%, based on the total weight of the composite (C).
17. The preparation method according to any one of claims 1-3, wherein, The mechanical exfoliation in step (2) includes one or more of the following methods and combinations: ball milling, sand milling, water bath ultrasonication, probe ultrasonication, high-speed shearing, high-pressure homogenization, and Taylor-Couette fluid exfoliation; and / or The melt blending in step (3) includes internal mixing, single-screw extrusion or twin-screw extrusion.
18. A modified graphene / polyolefin composite obtained by the method of any one of claims 1-17, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.05-25 wt%, based on the total weight of composite (C).
19. The modified graphene / polyolefin composite of claim 18, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.1-20 wt%, based on the total weight of composite (C).
20. The modified graphene / polyolefin composite of claim 19, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.15-15 wt%, based on the total weight of composite (C).
21. The modified graphene / polyolefin composite of claim 20, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.20-13 wt%, based on the total weight of composite (C).
22. The modified graphene / polyolefin composite of claim 21, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.25-12 wt%, based on the total weight of composite (C).
23. The modified graphene / polyolefin composite of claim 22, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.30-10 wt%, based on the total weight of composite (C).
24. The modified graphene / polyolefin composite of claim 23, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.35-9 wt%, based on the total weight of composite (C).
25. The modified graphene / polyolefin composite of claim 24, wherein the mass percentage of graphene, i.e. the mass fraction of graphene in composite C, is 0.40-8 wt%, based on the total weight of composite (C).
26. Use of the modified graphene / polyolefin composite according to any one of claims 18-25, characterized in that: It is used to reinforce polyolefins, to prepare polymer nanocomposites, to produce functional inks and coatings, as a raw material for producing high-performance modified polyolefin fibers through spinning technology, or as a raw material for producing antipathogenic nonwoven fabrics through meltblown technology.
Citation Information
Patent Citations
Method for directly preparing expanded graphite or graphene under normal temperature and normal pressure
CN105253878A
Method for preparing graphene modified polypropylene fibers by adopting supercritical fluid method
CN112064338A
Use method of mine polluted wastewater ecological restoration device
CN112174286A
Preparation method of polymer / graphene composite material through in situ reduction
CN101864098A
Method for preparing low oxidation degree graphene-modified polymethyl methacrylate (PMMA) composite material
CN105273114A